Solvent H-bond accepting ability induced conformational change and its influence towards fluorescence enhancement and dual fluorescence of hydroxy meta-GFP chromophore analogue. Issue 35 (17th August 2016) - Chatterjee, Tanmay; Mandal, Mrinal; Mandal, Prasun K.
Abstract : The effect of structural rigidity towards enhancement of fluorescence quantum yield of GFP chromophore analogues has been documented. Abstract : The effect of structural rigidity towards enhancement of fluorescence quantum yield of GFP chromophore analogues has been documented. In the present study, a new way of enhancing the fluorescence quantum yield of two ortho – meta GFP chromophore analogues meta -methoxy- ortho -hydroxy-benzylimidazolidinone (abbreviated as mOMe-HBDI) and meta -diethylamino- ortho -hydroxyl imidazolidinone (abbreviated as MOHIM) has been reported. This enhancement is controlled by the H-bond accepting ability (denoted as β value) of the solvent and happens only in the case of GFP chromophore analogues having ortho (hydroxyl)- meta (electron donating group) and not in the case of analogues having a para electron donating group. The ground state (solid) conformation of mOMe-HBDI has been obtained from single crystal X-ray analysis, exhibiting the existence of strong intramolecular H-bonding. However, in solution phase, as the solvent β value increases, the strength of intramolecular H-bonding decreases. This process has strong influence on the relative conformational orientation of phenyl and imidazolidinone rings. For mOMe-HBDI, fluorescence quantum yield increases with increase in β value of the solvents. However, the effect of solvent polarity cannot be completely ruled out. The lower wavelength emission band (∼480 nm) has been assigned to the normal charge-transferred (CT) species, whereas the highly Stokes shifted emission band (∼660 nm) has been assigned to the proton-transferred (PT) tautomer species for mOMe-HBDI. In solvents of low β value (say hexane) only the PT band and in solvents of high β value (say DMSO) only the CT band is observed. Quite interestingly, in solvents of intermediate β value both CT and PT bands, thus dual emission, are observed. For mOMe-HBDI when fluorescence decay is monitored at the normal CT emission band, it is observed to be biexponential in nature. The short component increases from ∼0.2 ns to 0.6 ns and the long component increases from 1 to 3.6 ns as the β value of the solvent increases. For a particular solvent, when fluorescence decay is monitored at the normal CT band, as the monitoring wavelength increases the amplitude of the long lifetime component increases and that of the short lifetime component decreases. Time-resolved area-normalised emission spectral (TRANES) analysis confirms the possible existence of two conformers having differential stabilisation by solvent polarity. When fluorescence decay is monitored at the PT band an instrument response limited (<60 ps) decay is noted. Strong support in favour of the above-mentioned structural, steady state and time-resolved optical observations and analyses has been obtained from the methoxy derivative mOMe-MBDI and MOMIM.